STRUCTURAL EQUATION MODELING (SEM-PLS) APPROACH: THE IMPACT OF WORKLOAD AND WORK-LIFE BALANCE ON TURNOVER INTENTION OF GENERATION Z IN BANDUNG CITY: Structural Equation Modeling (SEM-PLS) - Karmelia; Tangguh Dwi Pramono (Magister Manajemen Universitas Islam Malang, 2025)
This study aims to analyze the influence of workload and work-life balance on turnover intention among Generation Z employees in Bandung City. Generation Z is currently a dominant group in the workforce and tends to have unique characteristics, such as a preference for work flexibility and a high turnover rate. This research employs a quantitative approach involving 288 respondents who are Gen Z employees in Bandung. Data were collected through questionnaires and analyzed using SmartPLS 3 with the Structural Equation Modeling (SEM-PLS) approach. The results indicate that workload has a positive and significant effect on turnover intention, while work-life balance has a negative and significant effect. These findings suggest that an increase in workload tends to raise employees’ intention to leave, whereas maintaining a balance between work and personal life can reduce such intentions.